The impact of banks and stock market development on economic growth in South Africa: An ARDL-bounds testing approach - Sheilla Nyasha; Nicholas M. Odhiambo (Contemporary Economics, 2015)
This paper examines the impact of both bank- and market-based financial development on economic growth in South Africa during the period from 1980 to 2012. Unlike some previous studies, the current study employs means-removed average to construct both bank- and market-based financial development indices. The study uses the newly developed autoregressive distributed lag (ARDL) bounds testing approach to examine this linkage. The empirical results of this study show that there is a positive relationship between bank-based financial development and economic growth in South Africa. The results, however, fail to find any relationship between market-based financial development and economic growth in South Africa. The results apply irrespective of whether the regression analysis is conducted in the short run or in the long run. These results imply that it is bank-based financial development rather than market-based financial development that plays a pivotal role in propelling South Africa's real sector.
Keywords: G10; G20; O16; 330; South Africa; Bank-based Financial Development; Market-based Financial Development; Economic Growth